The Role of Herbal Medicine in Cholangiocarcinoma Control: A Systematic Review - Na-Bangchang, Kesara; Plengsuriyakarn, Tullayakorn; Karbwang, Juntra (Planta Medica, 2022)
The growing incidence of cholangiocarcinoma (bile duct cancer) and limited treatment options stimulate a pressing demand for research and the development of new chemotherapeutics against cholangiocarcinoma. This study aimed to systematically review herbs and herb-derived compounds or herbal formulations that have been investigated for their anti-cholangiocarcinoma potential. Systematic literature searches were conducted in three electronic databases: PubMed, ScienceDirect, and Scopus. One hundred and twenty-three research articles fulfilled the eligibility critera and were included in the analysis (68 herbs, isolated compounds and/or synthetic analogs, 9 herbal formulations, and 119 compounds that are commonly found in several plant species). The most investigated herbs were Atractylodes lancea (Thunb.) DC. (Compositae) and Curcuma longa L. (Zingiberaceae). Only A. lancea (Thunb.) DC. (Compositae) has undergone the full process of nonclinical and clinical development to deliver the final product for clinical use. The extracts of A. lancea (Thunb.) DC. (Compositae), Garcinia hanburyi Hook.f. (Clusiaceae), and Piper nigrum L. (Piperaceae) exhibit antiproliferative activities against human cholangiocarcinoma cells (IC50 < 15 µg/mL). Cucurbitacin B and triptolide are herbal isolated compounds that exhibit the most promising activities (IC50 < 1 µM). A series of experimental studies (in vitro, in vivo, and humans) confirmed the anti-cholangiocarcinoma potential and safety profile of A. lancea (Thunb.) DC. (Compositae) and its active compounds atractylodin and β-eudesmol, including the capsule pharmaceutical of the standardized A. lancea (Thunb.) DC. (Compositae) extract. Future research should be focused on the full development of the candidate herbs to deliver products that are safe and effective for cholangiocarcinoma control.
Keywords: cholangiocarcinoma; herbal medicine; anticancer activity; Atractylodes lancea (Compositae); Curcuma longa (Zingiberaceae); Garcinia hanburyi (Clusiaceae); Artemisia annua (Compositae); Zingiber officinale (Zingiberaceae); Andrographis paniculata (Acanthaceae)